Development of a Learning Module Based on Search, Solve, Create, and Share (SSCS) to Improve Students' Critical Thinking Skills - Erna Mawarni; Kaharuddin Arafah; Pariabti Palloan (Jurnal Penelitian Pendidikan IPA, 2026)
This study is a Research and Development (R&D) project employing the 4D model to develop an SSCS-based learning module. The primary focus of this research is to create a learning tool that is valid, practical, and effective in enhancing the critical thinking skills of tenth-grade students at SMAN 9 Gowa for the 2025/2026 academic year. Based on the validation results from three experts analyzed using the Aiken’s V formulation, the module was declared valid, with average scores of 0.71 for content feasibility, 0.89 for presentation, and 0.85 for language. Furthermore, the module demonstrated a high level of practicality based on teacher assessments, covering instructions 0.71, component coverage 0.73, and language 0.89. In terms of effectiveness, the N-Gain test results showed an improvement in critical thinking skills with a score of 0.59, placing the module in the effective category. Consequently, it can be concluded that the developed SSCS-based learning module meets all feasibility criteria and has proven successful in improving the quality of learning at the school.